Long term trends of seasonal and monthly rainfall in different intensity ranges over Indian subcontinent - VARIKODEN, HAMZA; KUMAR , K.KRISHNA; BABU, C.A. (MAUSAM, 2013)
Hkkjrh; xzh"edkyhu ekWulwu o"kkZ esa vf[ky Hkkjrh; xzh"edkyhu ekWulwu o"kkZ Ja`[kyk esa fdlh fo’ks"k izdkj dh izo`fRr dk lkekU;r% irk ugha pyk gS rFkkfi ISMR dh LFkkfud izo`fRr;ksa ds izHkkfor gksus dh fjiksVZ feyh gSA bl 'kks/k i= esa Hkkjrh; miegk}hi ds fofHkUu {ks=ksa esa xzh"edkyhu ekWulwu o"kkZ dh rhozrk dh fofHkUu Jsf.k;ksa dh nh?kZdkyhu izo`fRr;ksa dk irk yxkus dk iz;kl fd;k x;k gSA Hkkjr ekSle foKku foHkkx ds 1 tuojh] 1901 ls 31 fnlEcj] 2003 rd dh vof/k ds 1º ´ 1º v{kka’k&ns’kkarj fxzM ds LFkkfud foHksnu okys fxzM;qDr nSfud o"kkZ ds vk¡dM+ksa dk mi;ksx djds ekSleh vkSj ekfld o"kkZ dh nh?kZ vof/k izo`fRr Hkh rS;kj dh xbZA nf{k.k iwoZ] mRrj if’pe vkSj mRrj iwoZ {ks=ksa esa xzh"edkyhu ekWulwu o"kkZ dh izo`fRr esa c<+ksrjh fn[krh gSA tcfd e/; vkSj if’pe rVh; {ks=ksa esa deh dh izo`fRr n’kkZrh gSA ekfld iSekus ij] tqykbZ dh o"kkZ Hkkjr ds if’peh rVh; vkSj e/; {ks=ksa esa deh dh izo`fRr rFkk 0-1 izfr’kr egRoiw.kZ Lrj ij mRrjiwoZ {ks= esa fo’ks"k :i ls c<+ksrjh dh izo`fRr n’kkZrh gSA vxLr ekg ds nkSjku] if’peh rVh; LFkkuksa esa fo’ks"k :i ls 10 izfr’kr deh dh izo`fRr ikbZ xbZ gSA vf/kdka’k LVs’kuksa esa] ek/; nSfud o"kkZ ls de vkSj cgqr gh Hkkjh o"kkZ esa c<+ksrjh dh izo`fRr dk irk pyrk gSA lkekU; o"kkZ esa fofHkUu {ks=ksa ds fy, izo`fRr fHkUu&fHkUu gSA e/; vkSj nf{k.kh {ks=ksa esa lkekU; vkSj lkekU;r% mPp Jsf.k;ksa ls o`f) dh izo`fRr dk irk pyk gSA mPp vkSj vfr mPp rhozrk Jsf.k;ksa esa fo’ks"k :i ls deh dh izo`fRr dk irk pyrk gSA mRrj iwohZ {ks=ksa esa] 10 fe-eh-@fnu ls vf/kd dh o"kkZ 0-1 izfr’kr ds egRoiw.kZ Lrj ds lkFk egRoiw.kZ o`f) dh izo`fRr n’kkZrh gSA In general Indian summer monsoon rainfall did not show any significant trend in all Indian summer monsoon rainfall series, however, it was reported that the ISMR is subjected to spatial trends. This paper made an attempt to bring out long term trends of different intensity classes of summer monsoon rainfall in different regions of Indian subcontinent. The long term trend of seasonal and monthly rainfall were also made using the India Meteorological Department gridded daily rainfall data with a spatial resolution of 1° × 1° latitude-longitude grid for the period from 1st January, 1901 to 31st December, 2003. The summer monsoon rainfall shows an increasing trend in southeast, northwest and northeast regions, whereas decreasing trend in the central and west coastal regions. In monthly scale, July rainfall shows decreasing trend over west coastal and central Indian regions and significant increasing trend over northeast region at 0.1% significant level. During the month August, decreasing trend is observed in the west coastal stations at 10% significant level. In most of the stations, mean daily rainfall shows an increasing trend for low and very high intense rainfall. For the moderate rainfall, the trend is different for different regions. In the central and southern regions the trend of moderate and moderately high classes show increasing trend. And for the high and very high intensity classes, the trend is decreasing significantly. In the northeastern regions, above 10 mm/day rainfall shows significantly increasing trend with 0.1% significant level.